Elderly Veterans Receiving Care at a Veterans Affairs Medical Center While Enrolled in Medicare-Financed HMOs: Is the Taxpayer Paying Twice? - Passman, Leigh J (Blackwell Science Inc, 1997)
Elderly veterans who visit our Veterans Affairs (VA) Medical Center primary care clinic often mention they are enrolled in HMOs. Approximately 20% of patients hospitalized at our facility report health insurance coverage. Of 1,000 hospitalizations during a 6-month period in which veterans reported insurance coverage, 337 involved elderly veterans. Of these 337 hospitalizations, 218 (65%) were for 174 veterans who stated they were enrolled in a Medicare-financed HMO. The VA’s Medical Care Cost Recovery Program deemed only 46 (21%) of the hospitalizations billable and received reimbursement for 20 (9%). Thus, the VA is providing costly services already paid for by the Health Care Financing Administration under prepaid capitation contracts, and recovers minimal reimbursement from the HMOs.